Divine regie e umane variazioni. Bibbia e teatro in George Tabori (Altre Modernità, 2011)
The present contribution outlines George Tabori’s career as a playwright and a director in the time  span between 1947 and 2007 in American and European theatre, emphasizing his position as a ‘wise stranger’  in German post-war culture. Then, the intertextual and metaphorical presence of the Holy Scriptures in his  plays The Cannibals (1969), Mein Kampf (1987), and especially The Goldberg Variations (1991) is examined  with respect to the key issues of his production: anti-Semitism before, during and after the Holocaust and  its representation on the contemporary stage.